Steganography of Text Insertion into Image with End of File (EOF) Method - Sanbenfri Saragih; Eric Simanjuntak; Yebi Susani Rajagukguk; Diva Ferdinan Silalahi; Shevchenko Lumbanbatu (SEAN Institute, 2023)
Steganography is a technique for hiding information in digital media with the aim of maintaining data confidentiality. This study discusses the End of File (EOF) method for inserting text into digital images without changing the image pixels. This method works by adding text data in binary form to the end of the image file, which allows re-extraction without visual distortion. In this study, an experiment was conducted by inserting the text